The association between serum fatty acids and pregnancy in PCOS women undergoing ovulation induction. (2nd December 2022) - Li, Mingyue; Tian, Ye; Lv, Yonghuan; Xu, Yanping; Bai, Xiaohong; Zhang, Huijuan; Wang, Yanxia; Song, Xueru
Abstract: Background: Long-term dietary fat intake is thought to affect metabolism and pregnancy of polycystic ovary syndrome (PCOS) patients, and the type of fatty acids one consumes plays an important role. Previous studies mostly used questionnaires to analyze the type and proportion of fatty acids. Methods: This prospective study included 91 PCOS patients. Serum fatty acids were measured by the gas chromatograph-mass spectrometry method before ovulation induction. We compared the fatty acids between the pregnancy group and the nonpregnancy group and explored the influence of the fatty acids on live births and pregnancy loss. Results: Nervonic acid was lower in the pregnancy group than in the nonpregnancy group (0.25% vs. 0.30%, p = .017). The following trans-fatty acids were significantly lower in the pregnancy group than in the nonpregnancy group: trans-10-heptadecenoic acid, trans-vaccenic acid, trans-11-eicosenoic acid, and brassidic acid. The level of polyunsaturated fatty acids in the live birth group was significantly higher than the pregnancy loss group (16.95% vs. 15.10%, p = .039). Among individual PUFAs, the levels of linoleic acid ( p = .043), docosapentaenoic acid ( p = .024), alpha-linolenic acid ( p = .042), and eicosapentaenoic acid ( p = .035) were higher in the live birth group than in the pregnancy loss group. After adjusting for infertility duration, age, and body mass index, our findings suggested an inverse association between pregnancy and nervonic acid, trans-10-heptadecenoic acid, trans-vaccenic acid, trans-11-eicosenoic acid, and brassidic acid and pregnancy. Conclusions: Our findings indicate that polyunsaturated fatty acids are associated with live birth in PCOS patients. Serum trans-fatty acids and nervonic acid might be risk factors for nonpregnancy. The mechanism of the influence of different fatty acids on pregnancy and live birth merits further exploration.